Transplanted human photoreceptors transfer cytoplasmic material but not to the recipient mouse retina - Margaret T. Ho; Kotoe Kawai; Dhana Abdo; Lacrimioara Comanita; Arturo Ortin-Martinez; Yui Ueno; Emily Tsao; Azam Rastgar-Moghadam; Chang Xue; Hong Cui; Valerie A. Wallace; Molly S. Shoichet (Stem Cell Research & Therapy, 2024)
Abstract Background The discovery of material transfer between transplanted and host mouse photoreceptors has expanded the possibilities for utilizing transplanted photoreceptors as potential vehicles for delivering therapeutic cargo. However, previous research has not directly explored the capacity for human photoreceptors to engage in material transfer, as human photoreceptor transplantation has primarily been investigated in rodent models of late-stage retinal disease, which lack host photoreceptors. Methods In this study, we transplanted human stem-cell derived photoreceptors purified from human retinal organoids at different ontological ages (weeks 10, 14, or 20) into mouse models with intact photoreceptors and assessed transfer of human proteins and organelles to mouse photoreceptors. Results Unexpectedly, regardless of donor age or mouse recipient background, human photoreceptors did not transfer material in the mouse retina, though a rare subset of donor cells (< 5%) integrated into the mouse photoreceptor cell layer. To investigate the possibility that a species barrier impeded transfer, we used a flow cytometric assay to examine material transfer in vitro. Interestingly, dissociated human photoreceptors transferred fluorescent protein with each other in vitro, yet no transfer was detected in co-cultures of human and mouse photoreceptors, suggesting that material transfer is species specific. Conclusions While xenograft models are not a tractable system to study material transfer of human photoreceptors, these findings demonstrate that human retinal organoid-derived photoreceptors are competent donors for material transfer and thus may be useful to treat retinal degenerative disease.